2021
DOI: 10.1093/neuonc/noab103
|View full text |Cite|
|
Sign up to set email alerts
|

Environmental and sex-specific molecular signatures of glioma causation

Abstract: Background The relative importance of genetic and environmental risk factors in gliomagenesis remains uncertain. Methods Using whole-exome sequencing data from 1105 adult gliomas, we evaluate the relative contribution to cancer cell lineage proliferation and survival of single-nucleotide mutations in tumors by IDH mutation subtype and sex. We also quantify the contributions of COSMIC cancer mutational signatures to these tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“… 32 Of note, in agreement with prior findings by Le Rhun et al, 24 females were more likely to develop lymphopenia relative to males. These findings support recent work demonstrating broad-based sex differences in GBM, 33 as well as sex-based differences in hematologic adverse events in oncology patients. 34 …”
Section: Discussionsupporting
confidence: 91%
“… 32 Of note, in agreement with prior findings by Le Rhun et al, 24 females were more likely to develop lymphopenia relative to males. These findings support recent work demonstrating broad-based sex differences in GBM, 33 as well as sex-based differences in hematologic adverse events in oncology patients. 34 …”
Section: Discussionsupporting
confidence: 91%
“…TRA T2WI scans usually have smaller slice spacing, have the advantage of accurately constructing a 3D tumor ROI, and may allow for more accurate delineation of the tumor contour during segmentation. Additionally, previous research has confirmed that clinical features such as age and sex are related to glioma type [ 32 , 33 ]. Wu et al [ 34 ] developed a nomogram strategy to adopt clinical features in radiomics-based prediction models.…”
Section: Discussionmentioning
confidence: 81%
“…In addition, gliomas showed a male predominance, with males accounting for 58.21% (1492/2563) of the total study population and 64.56% (612/948) of glioblastomas. Sex-specific genetic signatures [ 26 ] have been found to predispose men to a 50% higher risk of being diagnosed with glioma than women [ 27 ]. In our study, we found that this difference was weakly correlated in WHO grade 3 tumors.…”
Section: Discussionmentioning
confidence: 99%